Relationship between Helicobacter pylori infection and gastrointestinal microecology - Xu, Wenting; Xu, Liming; Xu, Chengfu (Frontiers in Cellular and Infection Microbiology, 2022)
The prevalence of Helicobacter pylori (H. pylori) infection has exceeded 50% worldwide, and it is considered a high-risk factor for chronic gastritis, peptic ulcer, gastric adenocarcinoma, gastroesophageal reflux disease and functional dyspepsia. H. pylori drug resistance is a common problem worldwide. In recent years, the relationship between H. pylori infection and gastrointestinal microecology has received much attention. H. pylori infection changes the structure and composition of gastrointestinal microflora by regulating the gastrointestinal microecological environment, local pH value, cytokines and antimicrobial peptides, and immune response and then plays a crucial role in the occurrence and development of digestive system tumors, liver metabolism and extragastrointestinal diseases. The quadruple strategy of H. pylori eradication can also aggravate gastrointestinal microflora disorder. However, probiotics can reduce intestinal flora changes and imbalances through different mechanisms, thus enhancing the efficacy of H. pylori eradication therapy and reducing adverse reactions caused by eradication therapy. Therefore, this paper reviews the relationship between H. pylori infection and gastrointestinal microecology and its clinical application, providing a basis for clinical treatment.